Surprise! : The secret to customer loyalty in the service sector - Magnini, Vincent P. (New York, New York (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2015)
Modern consumers are bombarded with information from every angle. They can't handle it and, consequently, tune-out large portions of the information. Therefore, in order to gain their full attention, firms must find ways to surprise them during transactions--spawn mental script deviations for them. Research indicates that these script deviations can cement their loyalty. Therefore, Surprise! The Secret to Customer Loyalty in the Service Sector details how to create a surprise culture in a service firm.
Part I. Your customers are usually not paying attention -- 1. Information overload -- 2. Script deviation -- Part II. Surprise! -- 3. Stories from the hotel sector -- 4. Surprises in many forms -- 5. Novel surprise ideas -- Part III. Generating surprise ideas: an employee's perspective -- 6. Employees' motivation to surprise -- 7. Employees' ability to surprise -- 8. Expertise awareness in organizational relationships -- 9. Expertise access in organizational relationships -- Part IV. Generating surprise ideas: a customer's perspective -- 10. Rapport building with your customers -- 11. Feedback from your customers -- 12. Scanning the business environment for surprise ideas -- Final thought: 3 + 4 = 9 or 10 -- About the author -- Notes -- References -- Index.
Part of: 2014 digital library.
Includes bibliographical references (pages 111-119) and index.
Title from PDF title page (viewed on October 13, 2014).
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Service industries -- Customer services; Customer relations; Surprise; customer delight; customer service; customer surprise; services marketing; Electronic books